Prospects for defect engineering in Cu2ZnSnS4 solar absorber films. Issue 31 (12th May 2020) - Rudisch, Katharina; Davydova, Alexandra; Riekehr, Lars; Adolfsson, Joakim; Quaglia Casal, Luciano; Platzer-Björkman, Charlotte; Scragg, Jonathan
Abstract : Composition spread Cu2 ZnSnS4 thin films unveil the complicated interplay between process conditions and material properties, pointing to new approaches towards defect engineering. Abstract : Complex compound semiconductors, such as the emerging solar cell material Cu2 ZnSn(S, Se)4 (CZTS), present major experimental challenges in terms of understanding and controlling growth processes and defect formation. This study aims to shed light upon the complicated interplay of the synthesis conditions and CZTS thin film properties. Composition-spread thin films are fabricated in different atmospheric conditions during the annealing step. The span of the single-phase region is identified by a phase analysis combining XRD and Raman mapping. The phase characterisation is strengthened by STEM-EDX analysis. Our results show that the stability of the CZTS phase is strongly affected by the process conditions which is observed as a shift in the secondary phase boundaries and different levels of maximum cation ordering achieved in the different samples. With regard to the photoluminescence intensity, all investigated samples show the same trends: regions with Cu3 SnS4 secondary phase show the lowest intensity, while the presence of SnS x secondary phases greatly enhances the photoluminescence intensity. The single-phase region features an overall low photoluminescence intensity without a remarkable composition dependence and we propose the presence of deep defects in absence of secondary phases that limit the radiative recombination. We discuss implications for future efforts in defect engineering toward improving the efficiency of CZTS thin film devices.